Serum Copper Levels in Various Diseases: A Local Experience at Aga Khan University Hospital, Karachi - Siddiqui, Imran; Farooqi, Joveria Q.; Shariff, Dilsha A; Khan, Aysha H.; Ghani, Farooq (International Journal of Pathology, 2018)
Objective: To evaluate the possible alteration of serum copper levels in various clinical disorders using the method ofAtomic Absorption.Design: Descriptive analysisSetting: The Aga Khan University Hospital (AKUH) Clinical Laboratories Karachi, Pakistan (January 2000 to July 2001).Patients and Methods: 120 in-patients of AKUH were chosen through convenient sampling and their complete medicalrecords obtained from Health Information & Management System (HIMS). Their serum copper was then measured by FlameAtomic Absorption method (Shimazdu AA 6500). Patients were categorised as having infectious (36), GI and hepatic (14),cardiovascular (20), renal (10), pulmonary (15), malignant (7) and haematological (18) disorders. Test results were sorted intohigh, low or normal serum copper levels for each clinical category, frequencies calculated for each group, and the overallpercentage of normal, altered, high and low values determined.Results: Statistically significant (p<0.05) associations were seen between altered copper levels and infectious, GI & hepatic,renal, malignant and haematological disorders. Cardiovascular and pulmonary diseases also showed a high frequency ofabnormal results, but not significantly. Overall, 50% patients had serum copper levels greater than the normal mean + 2SD(115 μg/dl), while 27.5% had low serum Cu levels suggestive of Cu depletion whereas 22.5% showed normal values evenwith various clinical disorders.Conclusion: Alterations in Serum Copper, whether low or high, can give significant insight in disease process and should befurther studied as a reasonable marker of patient health.